Carbonylation of alkynes, alkenes and alcohols using metal complex catalysts - Sarkar, B. R.; Chaudhari, Raghunath V. (Catalysis Surveys from Asia, 2005)
Carbonylation of olefins, alcohols and halides using homogeneous as well as heterogeneous catalysts has been discussed. Highlights of contributions on the activity, selectivity and stability of catalysts for carbonylation reactions are discussed. Kinetics and mechanism including characterization of the intermediate catalytic species has also been reviewed. The performance of anchored Pd complexes on mesoporous supports (MCM-41 and MCM-48), water soluble Pd complexes and supported Pd catalysts in carbonylation of aryl alcohols and olefins has been discussed in the context of catalyst-product separation. Some aspects of kinetic modelling and reaction engineering of these multiphase catalytic reactions have also been reviewed.
Keywords: Carbonylation; catalysis; Heterogenization; homogeneous; Palladium

Rate enhancement in palladium catalyzed Heck reactions by Lewis acid promoters - Sud, Abhishek; Deshpande, Raj Madhukar; Chaudhari, Raghunath V. (Catalysis Communications, 2007)
Significant enhancement in the rate of Heck reactions has been achieved when catalytic amounts of Lewis acid (like FeCl(3)) promoters in the presence of trace amounts of water (> 2000 ppm) are used along with Pd complex catalysts. Experiments with different aryl halides, bases as well as olefins have been carried out to demonstrate the role of Lewis acid promoters. The increase in the reaction rates is due to the weakening of Ar-X bond by the Lewis acid in the manner similar to Friedel-Crafts reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Heck reaction; Lewis acid; Palladium; Promoters